Development of “Avic”Application as a Basic Level Communication for Autism Students - Nur’aini, Andini Prima; Junaidi, Ahsan Romadlon; Sunandar, Asep; Ediyanto, Ediyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Autism is a neurological disorder during development that results in a child having barriers, one of which is communication barriers, so that they require special guidance and services. An autistic person is also a visual learner, they receive information more easily visually than verbally or otherwise. Assistive technology has been widely used as a tool to help children with special needs, including autism. The Research use a TEACCH Method of PECS stage 1 until 3. Research and development of this application uses the RnD model (in Sugiyono) which consists of 10 stages, and researchers only took 9 stages, namely (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation , (5) Design Revision, (6) Product Trial (7) Product Revision (8) Usage Trial (9) Potential and problems. The validation subjects in this research were material experts, media experts and practitioners. The validation technique uses Aiken V. The data analysis technique uses non-parametric tests, quantitative percentage techniques, descriptive techniques for qualitative data. The results of the analysis produced application validation results with an average above 0.8, which means it is very feasible, and there is an increase in value when using the application by autistic students with basic communication